Comparative Effects of Yellow Root (Arcangelisia flava (L.) Merr.) Decoctions with Water and Brackish Water on Kidneys and Uterus in Wistar Rats - Suwijiyo Pramono; Risqika Y.T. Paramidhita; Marini Marini; Moch. Saiful Bachri (Majalah Obat Tradisional, 2020)
Yellow root (Arcangelisia flava (L.) Merr.) is a medicinal plant used traditionally in Borneo, Indonesia, for several diseases. Nevertheless, it contains berberine alkaloids that are considered harmful. Empirically, based on local wisdom people do not boil yellow roots with water but with brackish water. This study aimed to determine the effects of yellow root decoctions made using water and brackish water on blood biochemical and histopathological profile of kidneys and uterus in Wistar rats after subchronic treatment. Overall, 70 Wistar female rats were divided into seven groups of which three groups were given yellow root water decoctions and three groups were given yellow root brackish water decoctions with doses equivalent to 1.25 g/kg BW, 2.5 g/kg BW and 5 g/kg BW of dried yellow root, whereas the control group was only given Aquadest. After 28 days of treatments, blood samples were obtained for biochemical examination followed by a surgical examination to observe the histological features of the organs. The results revealed significant differences in the blood urea nitrogen (BUN) levels between group that was given water decoction of the yellow root and the control group. On the other hand, the groups that were given brackish water decoction revealed no significant changes, except at  the highest dose. Furthermore, histopathological features of rats treated using all doses of the yellow root water decoctions revealed organ damage compared with the normal group, manifested as hemorrhage, degeneration, and necrosis of the kidneys, as well as epithelial damage and inflammatory infiltration of the uterus.